The Reduction of Exhaust Emissions from a Diesel Engine by Using Biodiesel Blend - Ilkilic, C.; Behcet, R. (Taylor & Francis Inc, 2010)
Biodiesel has a great potential to reduce environmental pollution as an alternative fuel for diesel engines. The most important environmental problem is global heating up or green house effect caused by energy consumption. In this study, biodiesel produced from cottonseed oil was blended with diesel fuel, 20% biodiesel and 80% commercial diesel fuel, called B20, and used as a fuel in a direct injection diesel engine. The study aimed to test the emissions of a diesel engine using this blend and diesel fuel, and characterize gaseous emissions that are harmful to humans and the environment. Engine tests have been conducted with the aim of obtaining comparative measures of exhaust emissions, such as nitrogen oxide (NOx), carbon monoxide (CO), and carbon dioxide (CO2), and compute the behavior of the diesel engine running on the diesel fuel and the blend. The result showed on the emissions of the engine that were about 19% reduction in NOx, about 22% reduction in CO, and 13% reduction in CO2. The reduction in exhaust emissions has made biodiesel a suitable alternative for diesel engines and could contribute in controlling air pollution.
Keywords: alternative fuel; biodiesel; carbon dioxide; carbon monoxide; diesel engine